Kualitas Pelayanan Administrasi Kependudukan Di Kantor Camat Tomini Kabupaten Parigi Moutong - Nikmatusolikah; Mustainah; Mukarramah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aims to analyze the quality of population administration services at the Tomini District Office, Parigi Moutong Regency. The study employs the service quality theory developed by Zeithaml, Parasuraman, and Berry, which consists of five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A descriptive qualitative approach was applied in this research. The study involved five informants selected through purposive sampling based on their involvement in and knowledge of the implementation of population administration services. Data were collected through observation, interviews, documentation, and triangulation to ensure data validity. The findings indicate that the quality of population administration services at the Tomini District Office has not yet reached an optimal level. The dimensions of reliability and responsiveness were assessed as relatively satisfactory, as reflected in the employees’ ability to perform their duties in accordance with established procedures and their responsiveness in serving the public. However, challenges were still identified within the assurance and empathy dimensions, including insufficient employee discipline, delays in attendance, and service attitudes that did not consistently demonstrate friendliness and attentiveness to community needs. Furthermore, the tangibles dimension revealed limitations in service-supporting facilities and infrastructure, such as inadequate waiting areas and suboptimal service facilities. The lack of public dissemination regarding administrative procedures and requirements was also found to hinder service effectiveness. Therefore, efforts to improve human resource capacity, upgrade service facilities, and strengthen information dissemination are essential to achieving more effective, transparent, and citizen-oriented population administration services that meet public expectations and enhance community satisfaction.